2001
DOI: 10.1074/jbc.m105189200
|View full text |Cite
|
Sign up to set email alerts
|

Redox-dependent Gating of G Protein-coupled Inwardly Rectifying K+ Channels

Abstract: G protein-coupled inwardly rectifying K؉ channels (GIRK) play a major role in inhibitory signaling in excitable and endocrine tissues. The gating mechanism of these channels is mediated by a direct interaction of the G␤␥ subunits of G protein, which are released upon inhibitory neurotransmitter receptor activation. This gating mechanism is further manifested by intracellular factors such as anionic phospholipids and Na ؉ and Mg 2؉ions. In addition to the essential role of these components for channel function,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 57 publications
1
35
0
1
Order By: Relevance
“…Osmotically driven guard cell inflation is thereby inhibited and guard cell deflation is promoted, resulting in inhibition of stomatal opening, promotion of stomatal closure, and reduced plant water loss. Guard-cell K in currents share with GIRK channels the properties of inward rectification, activation by ATP, activation by PtdInsP 2 , and regulation by cellular redox status (9,10,(20)(21)(22)(23). We previously showed that genetic depletion of GPA1 relieves ABA inhibition of guard-cell K in currents (24,25).…”
mentioning
confidence: 99%
“…Osmotically driven guard cell inflation is thereby inhibited and guard cell deflation is promoted, resulting in inhibition of stomatal opening, promotion of stomatal closure, and reduced plant water loss. Guard-cell K in currents share with GIRK channels the properties of inward rectification, activation by ATP, activation by PtdInsP 2 , and regulation by cellular redox status (9,10,(20)(21)(22)(23). We previously showed that genetic depletion of GPA1 relieves ABA inhibition of guard-cell K in currents (24,25).…”
mentioning
confidence: 99%
“…Thiol/disulfide exchange reactions at the level of cysteine residues in proteins depend on the ϪSH group of GSH and have been suggested to regulate the progression of apoptosis (68,94), Thiol-exchange reactions might also be involved in the regulation of ion channels and changes in the ionic homeostasis of the cell. In fact, previous reports demonstrate that sulfhydryl groups within cytosolic cysteine domains of ion channels directly modulate channel activity (95)(96)(97).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to Cys-49 in Kir1.1, the accessibility of Cys-42 in Kir6.2 is reduced in the open state. In GIRK1/ GIRK4 heteromeric channels, the N-terminal cysteines were shown to mediate the redox modulation of channel currents (29). Zeidner et al (29) proposed that the neighboring lysines stabilize the oxidation of these cysteines, and as a result, mixed disulfides are formed by interaction with reduced glutathione, which inhibits channel activity.…”
mentioning
confidence: 99%
“…In GIRK1/ GIRK4 heteromeric channels, the N-terminal cysteines were shown to mediate the redox modulation of channel currents (29). Zeidner et al (29) proposed that the neighboring lysines stabilize the oxidation of these cysteines, and as a result, mixed disulfides are formed by interaction with reduced glutathione, which inhibits channel activity. The GIRK subunits also have a cysteine within the middle C terminus that is at the homologous position as Cys-308 in Kir1.1.…”
mentioning
confidence: 99%